Can we predict vascular status and culture result based through wound status in diabetic foot infection?. Issue 12 (March 2019) - Shin, Jin Yong; Roh, Si-Gyun; Chang, Suk Choo; Lee, Nae-Ho
Abstract : Abstract: Diabetic foot infection (DFI) should be treated by a multidisciplinary team to prevent amputation and morbid status. As physicians encountering DFI in outpatient clinic, a proper selection of antibiotic treatment and diagnostic approach for a vascular status is essential. We retrospectively investigated the patients with DFI from 2016 to 2017. All patients were examined for vascular status, wound status, and pathologic culture preceding the treatment. No statistical significance was observed between PEDIS grade 1 and 2 and 3 and 4 in culture status and culture results. Association analysis between vascular status and other variables, such as wound score and culture results, has no significant difference. Through these results, the helpful epidemiologic result of microbiology and necessity of examination for peripheral arterial disease were verified.